Sosialisasi Peningkatan Pemahaman Kesehatan Mental Pada Remaja - Neni Triana; Maya Apriani; Venny Mayumi Gultom; Ari Darmansyah (JURNAL PENGABDIAN KADER BANGSA, 2025)
Adolescence is a dynamic phase of development and undergoes many changes in the life of adolescents. One of these changes occurs in their mental condition. The changes that occur during adolescence can trigger mental emotional problems. The prevalence of mental emotional disorders has increased from 6.1%, or around 12 million people, to 9.8%, or around 20 million people. However, few adolescents seek professional help for their mental health problems and understanding of mental health in Indonesia tends to be low. This community service aims to increase the knowledge of adolescents regarding mental health. This community service was conducted at STIKes Budi Mulia Sriwijaya. The methods used in this community service are lectures and discussions involving students. The pre-test results showed a good knowledge level of 22.9%, sufficient by 39.5%, and less by 33.3%. After socialization, there was a change in the level of good knowledge by 52.1%, sufficient by 29.1%, and less by 14.5%. The existence of this education can increase the knowledge of adolescents to work together to maintain mental health and to know the causes, prevention, and treatment of mental illness.